Pembuatan Peta Resiko Kejadian ISPA Pada Anak Akibat Kebakaran Lahan Gambut di Kecamatan Kubu (Faculty of Health Sciences , Dr. Soetomo University, 2022)
Background: Forest and peatland fires in Indonesia is considered national and global disaster,almost every year forest and land fires occurred from 1997 to 2019. According to datafrom the Forest and Land Fire Management Unit (UPKHL) of the West KalimantanProvincial Forestry Service, up to October 2013, the number of hotspots in Kubu RayaRegency was 349 hotspots, including in the Kubu sub-district where researchersconducted the research.Objectives: the implementation of this research is to create a risk map for the incidence of ISPAin children in the Kubu sub-district, find out the demographic characteristics of theInflammatory Acute Disease (ISPA) in children community, create a threat map for theoccurrence of ISPA in children, and make a vulnerability map for the occurrence of ISPAin children in Kubu sub-district.Methods: This research is qualitative research with a descriptive explanation of the results. Theresearch data was taken using a google map to the respondent's address which had beenobtained from the Public Health ServicesResults: A map of the risk of pediatric ARI sufferers was obtained in the Kubu area along withthe risk of hotspots that might occur in the event of forest fires in the future.Conclusion: From the risk map obtained, it can be a reference for the community and localgovernment as well as various cross-sectors to prepare for health needs in the event ofanother forest fire so that it does not have too much impact on children and can causeISPA.